2010
DOI: 10.1128/ec.00374-09
|View full text |Cite
|
Sign up to set email alerts
|

A -Mating-Type Gene Expression Can Drive Clamp Formation in the Bipolar Mushroom Pholiota microspora (Pholiota nameko)

Abstract: In the bipolar basidiomycete Pholiota microspora, a pair of homeodomain protein genes located at the A-mating-type locus regulates mating compatibility. In the present study, we used a DNA-mediated transformation system in P. microspora to investigate the homeodomain proteins that control the clamp formation. When a single homeodomain protein gene (A3-hox1 or A3-hox2) from the A3 monokaryon strain was transformed into the A4 monokaryon strain, the transformants produced many pseudoclamps but very few clamps. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…In Agaricomycetes, the two classes of genes (those encoding pheromone receptors and HD1/HD2 transcription factors) are part of the MAT locus in bipolar systems (Supplementary Note 10). In the R. solani AG1 IA genome, we found the homologous HD1 (AG1IA_06139) and HD2 (AG1IA_08558) sequences to Pleurotus djamor , and we detected similar HD1/HD2 specific domains according to the homologous motifs in Basidiomycetes40. In the assembly, we did not find diverged HD1 and HD2 mating type genes, which would be expected in a diploid basidiomycete.…”
Section: Resultssupporting
confidence: 49%
“…In Agaricomycetes, the two classes of genes (those encoding pheromone receptors and HD1/HD2 transcription factors) are part of the MAT locus in bipolar systems (Supplementary Note 10). In the R. solani AG1 IA genome, we found the homologous HD1 (AG1IA_06139) and HD2 (AG1IA_08558) sequences to Pleurotus djamor , and we detected similar HD1/HD2 specific domains according to the homologous motifs in Basidiomycetes40. In the assembly, we did not find diverged HD1 and HD2 mating type genes, which would be expected in a diploid basidiomycete.…”
Section: Resultssupporting
confidence: 49%
“…bisporus H97 strain (as noted in a preliminary analysis [ 52 ]) and display several differences. The structure of the shorter gene β-fg1 with six introns (one after the start codon) and the length and amino-acid sequence of its protein are highly similar to the genes and proteins in C. cinerea [ 87 ], C. disseminatus [ 48 ], L. bicolor [ 86 ], Pholiota microspora [ 88 ] and Heterobasidion annosum [ 49 ]. The 220 aa-long product (ID 1137415) of β-fg1 shows 57–58% identity to the products of β-fg genes in C. disseminatus (AAZ14920), C. cinerea (EAU92782) and L. bicolor (EDR15176).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is likely that these functions are still controlled by the actions of pheromones and their receptors, but in the bipolar species, the MAT-A genes are now able to regulate the expression of these genes. More recently, Yi et al (85) showed that heteroallelism at MAT-A alone could drive both clamp cell formation and fusion in the bipolar species Pholiota microspora, suggesting some level of regulation of MAT-A genes on the normally MAT-B-regulated process of clamp cell fusion. Why loci controlling nuclear migration (MAT-B) should be regulated separately from the loci controlling conjugate nuclear division (MAT-A) is a longstanding mystery, as common MAT-A heterokaryons can form in tetrapolar species, but they produce a flat, unfit mycelium (62).…”
Section: Discussionmentioning
confidence: 99%